Effects of moxalactam and cefotaxime on rabbit renal tissue. - Luft, F C (1982)
To determine and compare the effects of moxalactam and cefotaxime on kidneys, we gave these drugs in doses of 750 and 1,500 mg/kg to rabbits for 7 days. Cephaloridine was included as a positive control. Neither moxalactam nor cefotaxime at either dose caused lysosomal enzymuria, changes visible by light microscopy or increased plasma creatine. Both drugs caused minor alterations in glomerular ultrastructure at the higher dose. Cephaloridine, on the other hand, caused widespread renal functional and morphological damage. We conclude that in rabbits, both moxalactam and cefotaxime are remarkably nonnephrotoxic.